Impact of Technology-Based Accounting Systems, Budgeting, and Cost Control on Company Profitability: A Case Study of SMEs in Indonesia - Annisa, Fadlia; Rafika, Mulya; Siregar, Muhammad Raja (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyse the influence of technology-based accounting systems, budgeting, and cost control on the profitability of case study companies in SMEs in Indonesia. This study is a quantitative descriptive study. The population in this study were SMEs and the sampling used purposive sampling technique with certain criteria on SMEs located in the city of Rantauprapat, which amounted to 98 respondents. Data analysis was carried out using the SEM (Structural Equation Modelling) method with the help of the SmartPLS application. The results showed that 1) technology-based accounting systems have a significant effect on company profitability, 2) budgeting has a significant effect on company profitability, 3) while cost control does not show a significant effect on profitability.